Analysis of The Influence of Environmental Behavior on The Water Balance of Kaligarang Watershed, Central Java - Hakim, Rohman (International Journal for Disaster and Development Interface, 2024)
The increasing population and land needs have led to changes in people's behavior towards the watershed, resulting in indications of disruption of the water balance. Therefore, it is necessary to investigate how community behavior affects the water balance of the Kaligarang watershed. This research is a combination of quantitative and qualitative approaches. The method of withdrawing respondents was purposive sampling. Data collection was done through observation, documentation, questionnaire distribution to respondents and interviews with key persons. Calculation of water balance using the Thorntwaite-Mather method. The results of the water balance calculation show that in periods 1 and 2 there was a surplus from December to April and a deficit from May to November. Deficits tend to increase while surpluses tend to decrease. From period 1 to period 2 the deficit increased by 142 mm and the surplus decreased by 316 mm. The tabulation results show that there are community behaviors that have a negative influence on water balance. This is reinforced by the results of interviews with key figures (key person) stating that environmental behavior has a negative influence on water balance.